Micro-optofluidic manipulation of particles - Soh, Kok Hong. (2009)
The method of optical manipulation of micro particles using optical tweezers was discovered many years ago. Since then, the field of optical tweezers went through many trials and experiments and had progress tremendously. The introduction of new techniques in optical tapping and manipulation was expanded to the trapping of live virus and bacteria using laser radiation pressure. This played a play a major role in the revolution in the field of biophysical and biochemical processes.